ANALISIS KEPERLUAN PEMBANGUNAN E-KANDUNGAN BERBASIS PROBLEM BASE LEARNING DALAM KURSUS ELEKTRONIKA DASAR DI PROGRAM STUDI PENDIDIKAN FIZIK (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThe aim of this research was to determine the needs of development e-content based the Problem Base Learning (PBL) in Basic Electronics Course ofphysics Education Study Program. Subjects in this research were experts PBL and e-content, lecturers of Physics education, students physics education consisting of 2 experts, 3 lecturers and 35 students.While the object of research is the requirements of development e-content based PBL in Basic Electronics course ofPhysics Education Study Program. In collecting data using questionnaires and data analysis using descriptive analysis.The findings show that the necessary development of e-contentbased PBL in Basic Electronics Course ofPhysics Education Study Program. This is evidenced through the feedback of students, lecturers, and experts from the questionnaire beginning with the high category.Key words: E-content, Problem Base Learning, needs analysis